Impact of weight loss for depressive symptom in mid-stage patients with Parkinson’s disease: a 4-year follow-up study - Kurihara, Kanako; Fujioka, Shinsuke; Mishima, Takayasu; Tsuboi, Yoshio (Frontiers in Neurology, 2024)
Introduction Weight loss is one of the non-motor symptoms frequently seen in patients with Parkinson’s disease (PwPD). Weight loss in PwPD is known to be negatively associated with motor and other non-motor symptoms and has been shown to influence the prognosis of PD. In this study, we followed weight change over a 4-year period in PwPD at a single institution and investigated the relationship between weight change and patients’ motor and non-motor symptoms. Methods PwPD who visited our hospital from January 2018 to December 2022 were enrolled. Body weights were measured at two points in 2018 (at the start of observation, ‘baseline’) and 2022 (at the end of observation, ‘end date’). In addition, motor symptoms, disease severity, cognitive function, and psychiatric symptoms were evaluated during the same period, and the relationship with weight loss was examined. Results Data of 96 PwPD were available for a 4-year follow-up. At baseline, the mean age was 65.7 ± 10.0 years, the mean disease duration was 6.8 ± 4.0 years, and the mean Hoehn and Yahr stage was 2.4 ± 0.7. Among them, 48 patients (50.0%) had a weight loss of ≥5% from baseline (weight loss group; mean loss was 6.6 ± 2.9 kg). The weight loss group was older (p = 0.031), had a lower Mini-Mental State Examination (MMSE) at baseline (p = 0.019), a significantly lower body mass index (p < 0.001), and a higher Zung Self-Rating Depression Scale (SDS) (p = 0.017) at the end date. There was a negative correlation (γ = −0.349, p < 0.001) between weight change and age, a positive correlation (γ = 0.308, p = 0.002) between weight change and MMSE at baseline, and a negative correlation (γ = −0.353, p < 0.001) between weight change and SDS at the end date. Age-adjusted correlations showed a final negative correlation (γ = −0.331, p = 0.001) between weight change and SDS. MMSE and age-adjusted correlations showed a low negative correlation (γ = −0.333, p = 0.001) between weight change and SDS at the end date. Conclusion Weight loss in PwPD in mid-stage was more likely with increasing age, and ≥ 5% weight loss was associated with worsening depression. Further research is needed regarding the significance of weight loss in PwPD.